Invasive Mechanical Ventilation of COVID-19 ARDS Patients - Singh, Vijay (2021)
The purpose of this review article is to analyse evidence on the use of ventilatory strategies and associated cointerventions in adult patients with COVID-19 induced acute respiratory distress syndrome (ARDS) and to provide treatment recommendations based on these interventions. For each recommendation mentioned, it is important to consider the quality of the evidence reviews thoroughly before applying these recommendations to specific clinical situations or policy decisions. No guideline or recommendations can consider all the compelling clinical features of individual patients, as they are unique. Thus, it is imperative that clinicians, patients, policy makers, and other stakeholders should not regard these recommendations as mandatory. However, this review article, impartially discusses the nuances of treatment available and management protocols followed in many centres around the world for the consumption of all treating physicians.